Diet for the prevention and treatment of Parkinson’s disease - Chen, Wenzhi; Fan, Ting; Xu, Renshi (Frontiers in Nutrition, 2025)
Parkinson’s disease (PD) is a common degenerative disease of the central nervous system with a variety of non-motor symptoms, in addition to the typical motor symptoms, which seriously affect the physical and mental health of patients, as well as their quality of life. All current treatment measures for PD only ameliorate and alleviate partial symptoms and signs in the early and middle stages. To date, no medicine or surgery can prevent PD progression. The search for preventive measures to treat and prevent PD is currently a research priority. Based on current related studies and investigations, diet interventions have now been found to play important roles in the treatment and prevention of PD. This article reviews recent research advances in diet in terms of polyphenols, fatty acids, vitamins, and dietary patterns for the prevention and treatment of PD.